The Impact of Corporate Governance on Sustainability Disclosure in Indonesian Listed Banks - Limbong, Artha Sary Br; Usman, Berto; Aujirapongpan, Somnuk (Indonesian Journal of Sustainability Accounting and Management, 2025)
Although sustainability reporting has gained attention in recent years, empirical evidence on the effectiveness of related regulations in Indonesia remains limited. Therefore, this study examines the influence of corporate governance on sustainability disclosure (SD) using panel data regression on 47 banks listed on the Indonesia Stock Exchange (IDX) from 2012 to 2022. The results indicate that the presence of a sustainability committee, audit committee, and CSR training has a significant impact on enhancing sustainability disclosure. In contrast, board age, board meetings, board independence, and the presence of women on the board showed no significant effect. These findings provide regulatory insights for developing sustainability frameworks and highlight the importance of internal structures in driving sustainability practices. The findings also align with international standards, such as the Global Reporting Initiative (GRI), the International Sustainability Standards Board (ISSB), and the EU’s Corporate Sustainability Reporting Directive (CSRD), which promote and, in some cases, require the integration of sustainability into corporate governance systems. This study challenges the applicability of traditional agency-based governance theories in emerging markets, where mechanisms like board independence have limited effectiveness. It also highlights the importance of adapting governance frameworks by incorporating stakeholder and legitimacy theories, providing fresh empirical evidence from emerging Asian economies. Moreover, the extended period and broad sample size contribute to the robustness of the findings, offering practical implications for policymakers and corporate leaders committed to advancing sustainability agendas.